2015
DOI: 10.1021/acs.jpca.5b06854
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Photoisomerization of Glycolaldehyde and Subsequent OH Radical-Initiated Oxidation of 1,2-Ethenediol

Abstract: It has recently been discovered that carbonyl compounds can undergo UV-induced isomerization to their enol counterparts under atmospheric conditions. This study investigates the photoisomerization of glycolaldehyde (HOCH2CHO) to 1,2-ethenediol (HOCH═CHOH) and the subsequent (•)OH-initiated oxidation chemistry of the latter using quantum chemical calculations and stochastic master equation simulations. The keto-enol tautomerization of glycolaldehyde to 1,2-ethenediol is associated with a barrier of 66 kcal mol(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 65 publications
(113 reference statements)
1
21
0
Order By: Relevance
“…we calculate a threshold of 272 kJ/mol, has been postulated as an atmospheric route to formation of HO • and formic acid (So et al, 2015), although it has not been experimentally observed.…”
Section: Other Carbonylsmentioning
confidence: 76%
See 1 more Smart Citation
“…we calculate a threshold of 272 kJ/mol, has been postulated as an atmospheric route to formation of HO • and formic acid (So et al, 2015), although it has not been experimentally observed.…”
Section: Other Carbonylsmentioning
confidence: 76%
“…S4l). This pathway has not been previously proposed for glycolaldehyde (Wallington et al, 2018;Bacher et al, 2001;Zhu and Zhu, 2010;Cui and Fang, 2011;So et al, 2015) and occurs via a 5-centre TS, which is lower in energy than the 4-centre TF TS for H 2 formation from the formyl and a β CH 2 hydrogen. Indeed it is the lowest energy dissociation pathway we have found in gylcolaldehyde.…”
mentioning
confidence: 66%
“…This alternative TF pathway has not been previously proposed in the photolysis of glycolaldehyde. 45,[63][64][65][66] Predicted S 0 TF thresholds are shown in Figure 3 below. In all cases but one, TF involves a sterically favourable 5-centre concerted TS involving H-loss from a β-hydrogen.…”
Section: Decarbonylation (Co-loss)mentioning
confidence: 99%
“…Recently, we reported on the isomerization mechanism of glycolaldehyde (HOCH 2 CHO), the archetypal α‐hydroxy carbonyl and an important tropospheric compound in its own right . This work revealed that glycolaldehyde could undergo keto‐enol tautomerization via intramolecular transfer of two H atoms, mediated by the hydroxyl group.…”
Section: Introductionmentioning
confidence: 99%